ANALYSIS OF STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITY ON MATRIX TOPICS: A CASE STUDY AT SMK AL MUHTADIN - Siti Nurlaila Antariksa; Huri Suhendri; Saring Saring (Nindikayla Institute, 2026)
Mathematical problem-solving ability is a fundamental competency that enables students to apply mathematical concepts to solve contextual problems. However, many vocational high school students continue to experience difficulties in solving non-routine mathematical problems, particularly in matrix topics. This study aimed to analyze students' mathematical problem-solving processes based on Polya's four-stage problem-solving framework. A qualitative case study approach was employed involving six eleventh-grade students from the Office Management and Business Services Program at a vocational high school in Indonesia. Participants were purposively selected to represent high, moderate, and low mathematical ability levels. Data were collected through written problem-solving tests, semi-structured interviews, and documentation and analyzed using the interactive model of Miles et al., while credibility was established through source and method triangulation. The findings revealed that students with high mathematical ability successfully completed all four stages of Polya's framework, whereas students with moderate ability generally experienced difficulties in evaluating their solutions. Students with low mathematical ability encountered difficulties from the initial stage of understanding the problem, resulting in inappropriate solution strategies and inaccurate conclusions. Overall, students' mathematical problem-solving performance was closely associated with their conceptual understanding, strategic reasoning, and reflective thinking. Therefore, mathematics instruction should emphasize systematic problem-solving strategies, conceptual understanding, and reflective learning practices to improve students' mathematical competencies. This study contributes to the literature by providing qualitative evidence of vocational students' mathematical thinking across different ability levels and offers practical implications for designing mathematics instruction that strengthens problem-solving and reflective thinking.